Electrifying Straetó : how to make it happen - Nina Victoria Rangel Ortiz 1985- (2014)
The use of electric vehicles in the public transport system of Iceland could contribute to achieve the government´s commitment of reducing CO2 emissions. The aim of this work is to determine the feasibility of converting the current diesel buses into an electric vehicle fleet. The study presents the analysis made to ten routes of the public system that operate in the Capital Area of the Country. Three different electric vehicle technologies were proposed to replace the current fleet of those ten routes. The simulation of the energy consumption from these technologies as well as their equivalent diesel version was made. The economic analysis for each technology and its respective diesel version was carried out. The results suggest that the proposed electric vehicles could replace the diesel buses without altering the current service provided by the public transport. The only obstacle for implementing electric vehicles is the high economic cost related to the battery lifetime of each technology. Key words: electric vehicles, battery lifetime, public transport, Iceland